Characteristics of development and dissemination of environmental management systems in the area of production of medicines in Ukraine - Zhurenko, Victoria V; Lebedynets, Viacheslav O (Ceska a Slovenska farmacie, 2022)
The article presents the results of a study based on an expert survey of senior management and leading experts of enterprises for the production of medicines in Ukraine and typical problematic aspects of implementing environmental management systems (EMS). It was found that among the enterprises whose respondents took part in the survey, only 25% implemented EMS and passed the certification procedure following the requirements of ISO 14001. A significant problem identified is the lack of influential information tools and methodological developments for the implementation, operation, and benefits of EMS in pharmaceutical production, especially to ensure processes regarding the readiness of enterprises to respond to emergencies. Insufficient support was noted, particularly in regulatory and financial incentives, and no benefits could encourage more efficient greening of pharmaceutical production. The negative consequence is the lack of interest of small and medium enterprises in investing in new technologies and sustainable business practices to reduce environmental pressures. EMS should be implemented as a part of the overall management system of the enterprise to manage environmental aspects, meet mandatory legal requirements and voluntary commitments in accordance with the objectives and environmental policy of the enterprise, as well as to address risks and opportunities. It is important to note the urgency of developing theoretical and methodological principles of design, implementation, and further development of EMS to increase the environmental efficiency of the enterprise, greening in medicines production, and achieving sustainable development goals.
Keywords: léčivé přípravky; farmacie; Ukrajina; zachování přírodních zdrojů; environmental management system; Pharmacy; ISO 14001; Commerce; EMS; pharmaceutical company; EMAS; environmental aspects; Conservation of Natural Resources; obchod; Ukraine; Pharmaceutical Preparations; production of medicines